Crossed fused Ectopic Kidney - A Case Report - Debnath, JC; Sarker, KP; Uddin, Md Nasir; Sarker, Sushanta K; Rahman, K Mahboobur; Rahman, AM Asif (TAJ: Journal of Teachers Association, 2009)
We present a case of crossed-fused ectopic left kidney in a young man who came with rightsided abdominal pain for about 5 months. Crossed-fused ectopic kidney is often associated with other congenital anomalies, especially in the urinary tract. Our patient had two anomalies-an anomalous placement of renal pelvis (laterally in the orthotopic kidney), and a high up caecum, which was an asymptomatic associated gastrointestinal tract anomaly. doi: 10.3329/taj.v16i2.3889 TAJ December 2003; Vol.16(2): 79-81